Case report: Resolution of lameness via compartmental resection of a malignant nerve sheath neoplasm of the median nerve in a dog - Smith, Jeffery; Kent, Marc; Glass, Eric; Davis, Garrett (Frontiers in Veterinary Science, 2025)
A 7-year-old golden retriever was evaluated for a 6-month history of progressive right thoracic limb lameness. A lameness (grade 3 out of 5 on visual gait analysis) and pain with palpation of the medial aspect of the brachium proximal to the elbow were identified on exam. Magnetic resonance imaging of the right thoracic limb revealed a well-delineated, ovoid mass arising from the median nerve just proximal to the elbow. Compartmental resection of the mass with limb preservation was performed. Microscopically, the mass was a malignant nerve sheath neoplasm. One week postoperatively, the lameness was mild (grade 1). Three months postoperatively, the lameness had resolved (grade 0). One year postoperatively, the dog’s gait remains normal. Malignant nerve sheath neoplasms commonly arise in the brachial plexus or cervical spinal nerves, often affecting the innervation provided by the radial nerve. Given its role in providing weight support, dysfunction of the radial nerve significantly impacts the gait. Conversely, dysfunction of the median nerve should not impair the gait. In the present case, compartmental resection of the neoplasm affecting the median nerve resolved the dog’s lameness. The return of normal limb function supports the contention that the lameness was consequent to general somatic afferent dysfunction, neuropathic pain, rather than general somatic efferent function (paresis).